Outbreak of Hemorrhagic Septicemia in Blackbuck (Antilope cervicapra) at Sri Sayajibaug Zoo, Vadodara, Gujarat: ClinicoPathology and Therapeutic Management - Pandya, Suchit S.; Patankar, Pratyush G.; Dave, Keshank M.; Rava, Sunant K.; Ghodasara, Dinesh J.; Bhanderi, Bharat B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Pasteurella multocida causes hemorrhagic septicemia (HS), an acute, often fatal, septicaemic disease in ruminants. It is commonly observed in the world’s tropical regions, especially in Asian and African countries. In the present study, eleven blackbucks (Antilope cervicapra) were diagnosed positive for hemorrhagic septicemia by using Leishman stain of blood smear showing bipolar organisms. The blackbucks were treated with bolus sulphadimidine @ 5 gm, powder uniselit @ 5 gm and liquid ostovet @ 25 mL per animal/day for seven days and after that bolus sulphadimidine @ 2.5 gm was given for the next three days. Following treatment eight blackbucks recovered and became normal. A post-mortem examination was performed on three blackbucks one died on first day and two blackbucks on the third day, which confirmed the changes typical of HS in lungs, liver and kidneys.